Présentation : sciences humaines et littérature. Conflits et complémentarité - Cambron, Micheline (Recherches sociographiques)

(untitled) (Département de sociologie, Faculté des sciences sociales, Université Laval, 2003)
AbstractWhat view should be taken of the relationships between the humanities and literature ? More specifically, how have considerations on language and discourse, arising out of literary theory and criticism, contributed to drawing the attention of geographers to new issues, and thus to calling into question their own discursive practices ?